MANEJEMEN PROSES DAN PENDEKATAN DALAM PEMBELAJARAN JARAK JAUH (PJJ) BERBASIS BLENDED LEARNING DI MADRASAH ALIYAH AL AZHAR KOTA BANJAR - Syamsudin; Suharyanto H Soro; Hisam Ahyani (Prodi MPI Fakultas Tarbiyah IAIN Madura, 2022)
The activities of educational institutions are currently still carrying out the learning process online. One of the learning innovations that can be carried out by schools is by implementing Distance Learning based on Blended Learning. This study aims to find out how the management, lesson planning, and evaluation of learning based on Blended Learning are carried out at MA Al Azhar, Banjar City. The number of respondents in this study consisted of 15 teachers spread across various fields of study. Research using qualitative data analysis techniques with descriptive methods. The results of the research show that at the planning stage, the school had previously formulated a special curriculum that was adapted to the Blended Learning learning model, this was also supported by very adequate learning facilities and infrastructure. At the implementation stage, there is a difference in the use of the learning approach with real events in the field, namely the shift in time in utilizing learning. MA Al Azhar the City of Banjar implements a part-time system in the use of learning, a week of face-to-face learning, and the following week an online system. At the evaluation stage, MA Al Azhar City of Banjar carries out face-to-face and online-based evaluations such as using evaluations through the results of recapitulation on Google Classroom and Exel on Google Classroom.